Scientometric Portrait of Vikram Ambalal Sarabhai: A Citation Analysis - Kademani, B. S.; Kalyane, V. L.; Kumar, Vijai (Journal of Information and Knowledge, 2000)
The paper analyses the citations to the publications of Vikram Sarabhai, using Science Citation Index 1944-1991as the source for data. The extent of citations received,in terms of the number of citations per paper and the categories of citing documents and the distribution of citations among them are determined. Analysing the year-wise break up of citations, the peak periods are identified. The extent of citations to the papers in each domain and the citation pattern in relation to the status of authorship are examined. Types of documents citing Sarabhai’s publications are identified. The citing journals are identified and ranked list of them is prepared. Distribution of citations and citing journals according to disciplines are made to asses the impact of Sarabhai’s research on other disciplines. By studying the distribution of citations among journals, the Bradford Multiplier is calculated and Bradford-Zipf citograph is plotted. Ten highly cited papers of Sarabhai have been identified. Prominent scientists citing Sarabhai’s publications are identified.The time-lag between publication of a paper and it receiving its first citation is estimated.